Al Bahr towers : the Abu Dhabi investment council headquarters - Oborn, Peter; Heathcote, Edwin; Denison, Edward; Ormsby, Eric (West Sussex : Wiley, 2013)
This publication is entirely centered on the design and delivery of Al Bahr Towers. With 300-colour images, it is highly visual with specially commissioned photography by Christian Richters. An illustrated introduction by the architectural correspondent of The Financial Times , Edwin Heathcote provides an engaging account of the background behind the building: the client, the circumstances behind the commission and its most significant architectural precedents. Expert insight is provided into the history and philosophy of Islamic architecture by Professor Eric Ormsby of The Institute of Ismaili Studies. A unique description of the design and procurement of these ground-breaking structures is provided by architectural author Edward Denison.
Keywords: Architecture -- United Arab Emirates -- Dubayy (Emirate).; Bank buildings -- United Arab Emirates